La Photographie en Dialogues = Dialoguizing Photography : The collections Instiut d'Art Contemporain - FRAC Rhone d'Art moderne de Saint-Etienne Métropole. - Chevrier, Jean-François; Dancer, Martine; Hegyi, Lóránd; Laclais, Bernadette; Lagrange, Richard; Maubant, Jean Louis; Snauwaert, Dirk; Thiollière, Michel; Exhibition. La Photographie à l'épreuve = Photography put to the proof (1). Exhibition. La Photographie à l'épreuve = Photography put to the proof (2). IAC (Institut d'Art Contemporain) Villeurbanne Rhône-Alpes. Musée d'Art Moderne de Saint-Etienne Métropole. 2005-02-10. 2005-02-11. 2005-04-10. 2005-05-22. les Collections de l'IAC - Frac Rhône-Alpes et du Musée d'art moderne de Saint-Etienne Métropole = Collections from the IAC - Frac Rhône-Alpes and the Museum of Modern Art, Saint-Etienne Métropole. les Collections de l'IAC - Frac Rhône-Alpes et du Musée d'art moderne de Saint-Etienne Métropole = Collections from the IAC - Frac Rhône-Alpes and the Museum of Modern Art, Saint-Etienne Métropole (Saint-Etienne Villeurbanne : FRAC Rhône-Alpes Villeurbanne IAC (Institut d'Art Contemporain) Villeurbanne Rhône-Alpes Musée d'Art Moderne de Saint-Etienne Métropole, 2005)
The photographic collections are the fruit of an important collaboration between the IAC - FRAC Rhône-Alpes and the Museum of Modern Art of Saint-Etienne. In 1985, the FRAC Rhône-Alpes originally commissioned art and photographic historian, Jean-François Chevrier, to build up a collection of works representing the history of photography. This led to the incorporation of works by the first generations of photographers - a thrilling and unexpected prospect for a regional body such as the FRAC. This collection was deposited to the Museum of Modern Art, thus nurturing the common interests of both parties and giving rise to two parallel, complementary collections as historical cross-sections spanning the main issues of photography. The natural outcome of such a longstanding collaboration was a large-scale twofold exhibition with the aim of bringing this rich cultural heritage to the public eye. This book, complete wich CD-Rom of the collections inventory, is therefore both a reminder of the exhibitions and a catalogue of the collections.
Baldus, Edouard ; Bayard, Hippolyte ; Collard, Auguste ; Thiollier, Félix ; Hausmann, Raoul ; Zwart, Piet ; Thalemann, Else ; Reinhart, Hans ; Molino, Carlo ; Boucher, Pierre ; Blanc, Théodore & Demilly, Antoine ; Albin-Guillot, Laure ; Parry, Roger ; Levitt, Helen ; Sander, August ; Evans, Walker ; Duval, Rémy ; Wols ; Oorthuys, Cas ; Ronis, Willy ; Jiru, Vaclav ; Lukas, Jan ; Cuallado, Gabriel ; Muller, Nicolas ; Facchetti, Paul ; Patellani, Federico ; De Biasi, Mario ; Monti, Paolo ; René-Jacques ; Keetman, Peter ; Henderson, Nigel ; Model, Lisette ; Franck, Robert ; Struth, Thomas ; Becher, Bernd & Hilla ; Ruff, Thomas ; Schoellkopf, Jean-Louis ; Killip, Chris ; Clark, Larry ; Adams, Robert ; Ray-Jones, Tony ; Bresson, Yves ; Josué, Ito ; Friedlander, Lee ; Batho, Claude ; Eggleston, William ; Klein, William ; Sherman, Cindy ; Mylayne, Jean-Luc ; Polke, Sigmar ; Saudek, Jan ; Faigenbaum, Patrick ; Coplans, John ; Horsfield, Craigie ; Milovanoff, Christian ; Lafont, Suzanne ; Auerbacher, Dominique ; Jouve, Valérie ; Bustamante, Jean-Marc
CD-rom zie speciale kast
biog. per kunstenaar
Engels
Frans
boek